Foreign CapitalInflows, Institutional Qualityand Technological Innovation: Effects on GDP Per Capita in Developing Countries (Journal of Asian Development Studies, 2026)
This study examinesthe impact of technology innovation, institutional quality and foreign capital inflows on economic growth and per capita income in developing countries using the data from 53 developing countries from 2002 to 2021. Various econometrics techniques are used for data analysis including cross-sectional dependence test, slope homogeneity test, CIPS and CADF test of unit root, panel co-integration test, FGLS model for parameter estimations, PCSE model for robustness estimation and Granger causality test. The outcomes showthat foreign capital inflows, institutional quality and technology innovations, laborforce participation, capital formulationand educational expenditures are positively and significantly linked to GDP per capita in developing countries, Panel Granger causality test indicates that there is a unidirectional causality between LFPR and GDPPC, and TI and GDPPC. Moreover, no causality is observed between FCIand GDPPC, education expenditures,and GDPPC in developing countries